2019
DOI: 10.1103/physrevd.100.084059
|View full text |Cite
|
Sign up to set email alerts
|

Examining the weak cosmic censorship conjecture by gedanken experiments for Kerr-Sen black holes

Abstract: In this paper, we investigate the weak cosmic censorship conjecture for the Kerr-Sen black holes by considering the new version of the gedanken experiments proposed recently by Sorce and Wald. After deriving the first two order perturbation inequalities in the low energy limit of heterotic string theory based on the Iyer-Wald formalism and applying it into the Kerr-Sen black hole, we find that the Kerr-Sen black hole cannot be overspun or overcharged by the charged matter collision after taking into account th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 36 publications
1
43
1
Order By: Relevance
“…Recently, Sorce and Wald suggested a new version of gedanken experiments to test the WCCC and found that it is valid for KN black hole under the second-order approximation of the collision matter source. Following this setup, it also has been investigated in various theories [29][30][31]33]. However, all of these theories only considered the case of the gravity coupled to nonlinear electrodynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sorce and Wald suggested a new version of gedanken experiments to test the WCCC and found that it is valid for KN black hole under the second-order approximation of the collision matter source. Following this setup, it also has been investigated in various theories [29][30][31]33]. However, all of these theories only considered the case of the gravity coupled to nonlinear electrodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Kerr-Sen black holes [33]. Although they showed that WCCC is well protected for the nearly extremal case of these black holes after considering the second-order perturbation inequality, there is still a lack of the general proof of the WCCC.…”
Section: Introductionmentioning
confidence: 99%
“…Under the first-order approximation of perturbation, it gives δ[T ab k a k b ] ≥ 0. Then, the first-order variational identity (34)…”
Section: Perturbation Inequalitiesmentioning
confidence: 99%
“…Most recently, based on this new version, WCCC has also been studied in the 5-dimensional Myers-Perry black holes [29], higher-dimensional charged black holes [30], charged dilaton black holes [31], RN-AdS black holes [32], static Einstein-Born-Infeld black hole as well as Kerr-Sen black holes [33]. Although all of them showed the validity of the WCCC in the new version of gedanken experiments, there is still a lack of the general proof of the WCCC.…”
Section: Introductionmentioning
confidence: 99%